Civil service reform in Japan and Korea: toward competitiveness and competency - Kim, Pan S. (2002)
Governmental problems still exist in Japan and Korea even though the two nations have achieved substantial economic and political development in modern times. Such problems include a low ranking in world competitiveness in government and a lack of competency. Furthermore, rigid and closed systems for employment and promotion still prevail without many improvements in human resource management. Recently, both the Japanese and Korean governments have paid serious attention to new challenges such as globalization and informatization. In order to improve competitiveness and competency, both governments have attempted to reform the civil service in more flexible and open manners. Japan and Korea as geographic neighbors have, in general, many similarities, although some may see more differences than similarities. This article cannot provide a full picture of both nations' governmental problems, but a study of civil service reform is meaningful for improving human resource management in the government of both countries as well as understanding Asian public personnel management. - Reproduced.
Keywords: Civil service reform - Japan; Civil service reform - Korea; Civil service - Japan; Civil service